2003
DOI: 10.1159/000073752
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethanol Exposure on Extraembryonic Vascular Development in the Chick Area Vasculosa

Abstract: The effect of ethanol (EtOH) exposure on extraembryonic vascular development was examined using the chick embryo area vasculosa (AV) in shell-less culture. Embryos were placed in cultures at Hamburger Hamilton (HH) stage 11/12 and a single dose of EtOH (10, 30 or 50%) was applied to the center of the blastodisc. Untreated/sodium-chloride-treated controls showed normal embryonic growth and well-developed extraembryonic vessels at 24/48 h of treatment. At doses of 30 and 50%, the mortality rate was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…In chick embryo, ethanol altered the early vascular development in area vasculosa in a concentration-dependent manner (Tufan and SatirogluTufan, 2003). The mechanisms proposed for the disruption were the generation of reactive oxygen species, perturbation of retinoic acid signaling, and alteration in the expression of growth regulatory vasculogenic factors and their receptors (Tufan and Satiroglu-Tufan, 2003). Reduction in cellular protein and RNA contents in medaka embryogenesis by ethanol (an index of oxidative stress) thus prompted us to extend our investigation to determine the status of oxidative stress and alcohol metabolizing enzyme mRNA levels in medaka embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In chick embryo, ethanol altered the early vascular development in area vasculosa in a concentration-dependent manner (Tufan and SatirogluTufan, 2003). The mechanisms proposed for the disruption were the generation of reactive oxygen species, perturbation of retinoic acid signaling, and alteration in the expression of growth regulatory vasculogenic factors and their receptors (Tufan and Satiroglu-Tufan, 2003). Reduction in cellular protein and RNA contents in medaka embryogenesis by ethanol (an index of oxidative stress) thus prompted us to extend our investigation to determine the status of oxidative stress and alcohol metabolizing enzyme mRNA levels in medaka embryos.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear evidence that there is any significant difference between data derived using in ovo or shell-less culture method [103]. In order for the chick embryos to develop, eggs must be maintained at 37 o C, in a humidified atmosphere [103][104][105][106][107][108]. The first day in these conditions is considered to be day 1 of embryonic development.…”
Section: Culture Methods Used In Cam Assaymentioning
confidence: 99%
“…Satiroglu-Tufan found that the exposure of (10, 30 or 50%) ethanol could increase the embryonic mortality rate and inhibit the vascular development in a dose-dependent manner during latter developmental stages of chick embryos [41]. In this study, gastrula chick embryo (earlier stages) is used as a model to investigate the effects of 2% ethanol exposure on early vascular development.…”
Section: Discussionmentioning
confidence: 96%